Is Long-Term Prognosis for Pervasive Developmental Disorder Not Otherwise Specified Different from Prognosis for Autistic Disorder? Findings from a 30-Year Follow-Up Study - Groholt, Berit (2011)
We followed 74 children with autistic disorder (AD) and 39 children with pervasive developmental disorder not otherwise specified (PDD NOS) for 17–38 years in a record linkage study. Rates of disability pension award, marital status, criminality and mortality were compared between groups. Disability pension award was the only outcome measure that differed significantly between the AD and PDD NOS groups (89% vs. 72%, p < 0.05). The lower rate of disability pension award in the PDD NOS group was predicted by better psychosocial functioning. The lack of substantial differences in prognosis between the groups supports a dimensional description of autism spectrum disorder, in line with proposed DSM-V revision